Interaction of the SAC/SIC Behavioral Systems in Alcohol Consumption Among University Students and the Variability According to Sex - Toscano Rodríguez, Freddy (2026)
This study examines the interaction between Behavioral Activation System (BAS) and Behavioral Inhibition System (BIS) and their influence on alcohol consumption in university students, exploring sex differences. Reciprocal moderation models were applied to a sample of 336 students (123 males, 213 females). Results show that the relationship between BAS and alcohol consumption is moderated by BIS, and vice versa, with stronger inhibitory effects when the opposite system is at low levels. In males, the interaction between BAS and BIS is significant, suggesting a balance between approach and avoidance that influences drinking behavior. In females, BAS emerges as a consistent inhibitory predictor regardless of BIS level, with a negative beta coefficient, indicating that higher behavioral activation is associated with lower consumption, possibly due to neurobiological and motivational sex differences. These findings support Reinforcement Sensitivity Theory and highlight the need for personalized prevention and intervention approaches considering motivational profiles and sex.